Abnormalities of the Optic Nerve in Down Syndrome and Associations With Visual Acuity - Postolache, Lavinia (Frontiers in Neurology, 2019)
Background: Various ocular anomalies are present in the vast majority of individuals with Down syndrome; however, we know little about optic nerve abnormalities. The aim of this cross-sectional comparative study was to describe optic disc morphology in patients with Down syndrome and to determine if the differences found are potentially related to visual acuity. Subjects/methods: Assessable fundus images were obtained in 50 children with Down syndrome and 52 children without Down syndrome. Morphological analysis of the optic nerve was performed, including the disc-to-macula distance (DM) to disc diameter (DD) ratio (DM/DD), the cup-to-disc ratio and optic disc ovality. Data relating to ophthalmological status were retrospectively analyzed to evaluate the possible causes of reduced visual acuity. Results: DM/DD was significantly larger (p=0.0036) and the cup-to-disc ratio was significantly smaller (p=0.018) in children with Down syndrome, compared to controls. The optic discs were also more frequently torted (p=0.034), tilted (p=0.0049) and oval (p=0.026). Furthermore, crescents (p=0.0002), peripapillary atrophy (p=0.0009) and pigment anomalies (p<0.0001) were also more prevalent in children with Down syndrome than in those without. Visual acuity was significantly lower in children with Down syndrome compared to controls with similar refraction problems and strabismus prevalence (p<0.0001). The mean DM/DD and the presence of a crescent was not directly related to visual acuity (r=0.39, p=0.31), (r=0.35, p=0.12) respectively. Visual acuity was diminished in 80% of children with Down syndrome and the smallest discs and in 84% of those with tilted discs. However, other causes may contribute to the diminished visual acuity in these cases. Conclusion: The optic nerve head in children with Down syndrome is affected by various anatomical and developmental abnormalities. Unrelated to refraction (spherical equivalent), the optic discs appear smaller and more frequently mal-inserted in Down syndrome. Optic disc hypoplasia, as well as severe tilting, may reduce vision, but they do not represent major contributors to the decrease of vision in such children. As these children often have multiple ocular and neurosensory problems, it remains challenging to relate visual acuity problems with a specific abnormality. Smaller discs may lead to optic disc drusen formation in children with Down syndrome.